The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/1971295
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for Metabolic Syndrome via TCM Pattern Differentiation: Tongue Diagnosis for Predictor

Abstract: Metabolic syndrome is a morbid condition, which is manifested by central obesity, abnormal glucose tolerance, lipodystrophy, and hypertension. Traditional Chinese medicine (TCM) clarifies that obesity is classified as phlegm-dampness. It is often accompanied with qi stagnation and blood stasis. One hundred and two overweight adults, who did not receive lipid-lowering drugs, were enrolled for analysis. The exclusion criteria were adults having malignancy disease, DM, and renal disease or who were pregnant or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Because tongue diagnosis has the advantages of intuition and simplicity, some scholars have recently discovered the importance of the tongue image for the diagnosis and prognostic prediction of diseases[ 22 , 23 ]. The oral microbiota varies according to the different sampling sites with a high diversity[ 24 ], but as the tongue texture and tongue color form an important basis for diagnosis and treatment in TCM[ 25 ]. The treatments adopted for patients with white and yellow tongue coatings are different, thus, the tongue coating oral microbiotas were selected for analysis in our study, and the samples were grouped by the color of the tongue coating.…”
Section: Discussionmentioning
confidence: 99%
“…Because tongue diagnosis has the advantages of intuition and simplicity, some scholars have recently discovered the importance of the tongue image for the diagnosis and prognostic prediction of diseases[ 22 , 23 ]. The oral microbiota varies according to the different sampling sites with a high diversity[ 24 ], but as the tongue texture and tongue color form an important basis for diagnosis and treatment in TCM[ 25 ]. The treatments adopted for patients with white and yellow tongue coatings are different, thus, the tongue coating oral microbiotas were selected for analysis in our study, and the samples were grouped by the color of the tongue coating.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome is one of the manifestations of endocrine system disorders; it manifests by central obesity, abnormal glucose tolerance, lipodystrophy, and hypertension [50]. Obesity is often accompanied by Qi stagnation and blood stasis and is classified as phlegm dampness in TCM (manifested by a white coating).…”
Section: Close Correlation Between Tongue Coating and Diseasementioning
confidence: 99%
“…Obesity is often accompanied by Qi stagnation and blood stasis and is classified as phlegm dampness in TCM (manifested by a white coating). Lee et al [50] found that the TC in the non-metabolic-syndrome group was white in about 79.6% and yellow in 20.4% of the patients, while the metabolic-syndrome group had a white coating in 100% and a yellow coating in 0%. The difference between the groups is significant (P = 0.002).…”
Section: Close Correlation Between Tongue Coating and Diseasementioning
confidence: 99%
“…In China, integrative medicine combines traditional Chinese medicine (TCM) and modern medicine for clinical practice [1][2][3]. The diagnosis of integrative medicine comprises the clinical diagnosis of modern medicine and syndrome pattern diagnosis [4]. Syndrome pattern based on TCM theory is an outcome of the analysis of TCM information by the TCM practitioner, and TCM treatments rely on it [4].…”
Section: Introductionmentioning
confidence: 99%